A three-level framework to evaluate airline service quality based on interval valued neutrosophic AHP considering the new dimensions - Kavus, Bahar Yalcin; Tas, Pelin Gulum; Ayyildiz, Ertugrul; Taskin, Alev (ELSEVIER SCI LTD, 2022)
Measuring customer satisfaction in service businesses is very important in terms of both increasing service quality and meeting customer expectations. Up-to-date and comprehensive quality of service measurement techniques provide important information to the companies about the way customers perceive the quality and their service quality expectations. It is critical to measure the service quality for airline transportation, which is becoming more popular compared to other types of transportation and therefore increasing competition. In order to compete in the market and improve their service quality, companies should know their customers well and make improvements by analysing their expectations correctly. In this context, the SERVQUAL method is one of the frequently preferred and effective tools in service quality measurement. However, it is not possible to deal with the effects of radical changes such as the development and transformations of technology, events and trends under the influence of the world with the conventional SERVQUAL method. For this purpose, the traditional method consisting of five dimensions has been extended to nine dimensions by adding four more dimensions, namely Environment, Pandemic, Digital Technology and Information Systems. While it is possible to perform a more detailed service quality measurement with the proposed method, companies are provided with an effective and up-to-date tool to determine which dimensions are more important. In this study after structuring main dimensions and its inner levels hierarchically, Modified Delphi method is applied to a group of experts and the main criteria are evaluated with Best Worst Method and sub-criteria are evaluated with Interval-Valued Neu-trosophic AHP method. After subjecting the criteria, whose importance are determined, to sensitivity analysis, the results obtained are evaluated in terms of airline transportation and recommendations are presented. In addition to the extended approach it proposes, this study is the most detailed research on airline service quality as far as we know.
Keywords: SERVQUAL; Best worst method; IVN-AHP Method; Airline; COVID-19; HEALTH-CARE; CUSTOMER SATISFACTION; HYBRID APPROACH; EXPECTATIONS; PERCEPTIONS; Transportation